Evaluation of long-term stability of mesiodistal axial inclinations of maxillary molars through panoramic radiographs in subjects treated with Pendulum appliance - Caroline Andrade Rocha; Renato Rodrigues de Almeida; José Fernando Castanha Henriques; Carlos Flores-Mir; Marcio Rodrigues de Almeida (Dental Press Editora, 2016)
Objective: To evaluate the stability of mesiodistal inclination of maxillary molars produced by a pendulum appliance, five years after completion of orthodontic treatment. Angulation changes were compared to an untreated sample. Methods: The sample consisted of 20 patients (14 females and 6 males) with Class II, Division 1 malocclusion that was treated through molar distalization with a pendulum appliance followed by cervical headgear and full fixed appliances. Maxillary molar inclination was evaluated through panoramic radiograph. The mean age at pretreatment was 14.3 ± 1.6 years, whereas at immediate post-treatment it was 18.6 ± 1.8 years, and at long-term post-treatment it was 23.8 ± 2.0 years. A control group of 16 untreated individuals with untreated normocclusion ranging in age from 12 to 17 years old were used as comparison group. Data were statistically analyzed with independent t-tests and ANOVA test followed by Tukey post-hoc tests. Results: Statistically significant differences were found between T1(94.50) and T2 (98.80) as well as between T2 and T3 (94.70) for maxillary first molars. Maxillary second molars did not show any statistically significant positional changes during the evaluated time periods T1 (107.50), T2 (109.30) and T3 (106.90). Conclusion: Although maxillary first molars underwent distal crown inclination immediately after treatment, approximately five years thereafter their roots tended to upright close to the pretreatment positions.